Single or paired?: Structure and reactivity of PNP-chromium(II) hydrides - Ott, Jonas C.; Isak, Daniel; Melder, Julian J.; Wadepohl, Hubert; Gade, Lutz H. (Inorganic chemistry, 2020)
The preparation and reactivity of a range of novel paramagnetic chromium(II) complexes supported by a carbazole-based PNP pincer ligand is reported. Deprotonation of the ligand precursors R(PNP)H (1R) and subsequent reaction with chromium(II) chloride led to the formation of square-planar chlorido complexes R(PNP)CrCl (2R). Further reaction with various alkylating agents resulted in the isolation of chromium alkyl complexes R(PNP)CrR′ (3R-R′) which were then hydrogenated to yield two rare examples of paramagnetic chromium(II) hydrides 4iPr and 4tBu. Both compounds were characterized by X-ray diffraction and paramagnetic NMR spectroscopy supported by a comprehensive DFT-supported assignment of the resonances. While the di(tert-butyl)phosphino PNP substituted complex 4tBu was found to exhibit a monomeric square-planar molecular structure, its isopropyl-substituted analog 4iPr forms a dimer, also indicated by a strong antiferromagnetic coupling of the chromium centers. The pronounced reactivity of these compounds toward C═X double bonds was demonstrated by reaction with benzophenone, N,N′-dicyclohexylcarbodiimide, and carbon dioxide, which gave the corresponding insertion products. The alkoxido complex 5iPr, the amidinato complex 6iPr, and the formato compound 7tBu were also characterized by X-ray diffraction.